Ο λαϊκιστικός λόγος στη Δυτική Ευρώπη: Ανάλυση Λόγου και Μεταφραστικές Προκλήσεις. Το γαλλικό Rassemblement National και το ισπανικό VOX ως μελέτες περίπτωσης. - (:unkn) unknown (My University, 2022)
Η εργασία που ακολουθεί συντάχτηκε ως μεταπτυχιακή διπλωματική εργασία στα πλαίσια του Προγράμματος Μεταπτυχιακών Σπουδών του Τμήματος Ξένων Γλωσσών, Μετάφρασης και Διερμηνείας του Ιονίου Πανεπιστημίου για το Γ’ εξάμηνο και το ακαδημαϊκό έτος 2021-22. Κεντρικό αντικείμενο της εργασίας είναι η ανάλυση του πολιτικού εκείνου λόγου που θα χαρακτηρίζαμε λαϊκιστικό (populist discourse), ενώ, πλάι στην ανάλυση αυτή, πραγματοποιείται και αναφορά στη μετάφραση πολιτικού λόγου και συγκεκριμένα στις προκλήσεις που έθεσαν στον γράφοντα τα κείμενα πολιτικού λόγου των υπό εξέταση πολιτικών κομμάτων.

The following was written as a postgraduate thesis within the framework of the Master’s Programme ‘Science of Translation’ offered by the Department of Foreign Languages, Translation and Interpretation of the Ionian University. The thesis was submitted during the academic year 2021- 22 and the third semester of the aforementioned Master’s Program. The main focus of this thesis is the analysis of the kind of political discourse that we would define as populist, while, alongside this analysis, a reference is made to the translation of populist discourse and specifically to the challenges that it can pose to the subject performing the translation. The thesis revolves around the political discourse communicated by the political leaders of two parties of the so-called Popular Right or Extreme Right in France and Spain. The consequent translation of their words into Greek is also worth commenting, due to the very nature of populist discourse.
Populist discourse in Western Europe: Critical Discourse Analysis and Translation Challenges
Keywords: Ανάλυση Λόγου, λαϊκιστικός λόγος, λαϊκισμός, Εθνικό Μέτωπο, Λεπέν, Αβασκάλ; populism, Critical Discourse Analysis, VOX, Rassemblement National, Abascal, LePen